Bahasa Gaul “Jaksel” Sebagai Eksistensi Di Kalangan Remaja Jakarta - Haura Asqo Balqis; Sheryl Delvina Aurora Anggoro; Aniek Irawatie (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
Language is used as a means of communication between individuals with each other, both orally and in writing. Thealteration causes an increase in the type of language over time and gives rise to many new languages. As of now, thereis a dominant language in society, namely slang. Slang itself has existed for a long time, known as program language.Slang is a non-standard language, this language is usually used by teenagers when they communicate. One exampleof this slang is the slang "Jaksel" which is very popular among young people in Jakarta, especially teenagers in SouthJakarta. Because the use of "Jaksel" slang is very widespread among Jakartan teenagers, therefore the purpose of thisstudy is to find out "Jaksel" slang existence among Jakartan teenagers. This study uses a qualitative descriptive methodwith interview techniques proposed to youth sources in Jakarta. The results showed that South Jakarta slang is seenin the existence of Jakarta teenagers because this language is a unique language with a mixture of Indonesian andEnglish and is widespread in social media circles. Thus, South Korean slang is considered something that exists inIndonesia. among young people in Jakarta because of the impact of social media which causes the language to becomea trend.